The Comprehensive AOCMF Classification System: Fracture Case Collection, Diagnostic Imaging Work Up, AOCOIAC Iconography and Coding. Issue 1 (December 2014) - Cornelius, Carl-Peter; Kunz, Christoph; Neff, Andreas; Kellman, Robert M.; Prein, Joachim; Audigé, Laurent
The AO classification system for fractures in the adult craniomaxillofacial (CMF) skeleton is organized in anatomic modules in a 3 precision-level hierarchy with account for an increasing complexity and details. Level-1 is most elementary and identifies no more than the presence of fractures in 4 separate anatomical units: the mandible (code 91), midface (92), skull base (93) and cranial vault (94). Level-2 relates the detailed topographic location of the fractures within defined regions of the mandible, central and lateral midface, internal orbit, endo- and exocranial skull base, and the cranial vault. Level-3 is based on an even more refined topographic assessment and focuses on the morphology — fragmentation, displacement, and bone defects — within specified subregions. An electronic fracture case collection complements the preceding tutorial papers, which explain the features and options of the AOCMF classification system in this issue of the Journal. The electronic case collection demonstrates a range of representative osseous CMF injuries on the basis of diagnostic images, narrative descriptions of the fracture diagnosis and their classification using the icons for illustration and coding of a dedicated software AOCOIAC (AO Comprehensive Injury Automatic Classifier). Ninety four case examples are listed in two tables for a fast overview of the electronic content. Each case can serve as a guide to getting started with the new AOCMF classification system using AOCOIAC software and to employ it in the own clinical practice.